Perawatan Kehamilan Yang Sehat: Tips Untuk Ibu Hamil - Susanti Susanti; Sastrika Handayani Marpaung; Cakrawati R; Lumastari Ajeng Wijayanti; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Pregnancy is a crucial period in a woman's life that requires special attention to maintain the health of both mother and fetus. Lack of knowledge and awareness regarding healthy prenatal care can increase the risk of complications, including anemia, hypertension, and premature birth. Objective: This study aims to identify healthy prenatal care practices, factors influencing maternal health, and develop evidence-based recommendations for pregnant women in Indonesia. Methods: This study used a descriptive qualitative approach, collecting data through in-depth interviews with 20 pregnant women and five health workers in Sleman Regency, as well as literature review from national and international journals. Data were analyzed thematically to identify patterns of care and determinants of maternal health. Results: The study identified five main aspects of healthy prenatal care: (1) implementing a balanced, nutritious diet, (2) routine prenatal checkups at least six times during pregnancy, (3) light physical activity and adequate rest, (4) social and emotional support from the family, and (5) increasing health education through medical personnel and digital media. These five aspects contribute significantly to reducing the risk of pregnancy complications. Conclusion: Healthy pregnancy care requires a synergy between medical knowledge, social support, and a healthy lifestyle. Collaboration between health professionals, families, and the government is needed to strengthen the community-level education system for pregnant women.